(untitled) (Western European Journal of Medicine and Medical Science, 2025)
This study examined the digital transformation of electronic health systems (EHRs), their benefits in health practice, and the challenges that arise. Based on the results of literature analysis, statistics and empirical surveys, the role of EHR systems in enhancing patient safety, supporting clinical decisions, and reducing medical malpractice has been analyzed. The results showed the need for integration, cybersecurity and compliance with regulatory requirements to improve the efficiency of systems.